2020
DOI: 10.1055/a-1027-6511
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Intensity Interval Training on Physical Parameters, Metabolomic Indexes and Serum Ficolin-3 Levels in Patients with Prediabetes and Type 2 Diabetes

Abstract: Background Exercise benefits people with abnormal glucose metabolism, and serum ficolin-3 levels have been reported to be associated with diabetes. However, no relevant study has discussed the relationship between high-intensity interval training (HIIT) and ficolin-3 in a Chinese population. Objective To compare the effect of HIIT and moderate-intensity continuous training (MICT) on blood pressure, glucose control, the lipid profile and the serum ficolin-3 level in patients with prediabetes and type 2 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Ficolin-3 can activate the complement system via the lectin pathway (133), plays roles in bacterial defenses (134,135) and autoimmunity (136,137) and is modulated in viral infections including HIV (138). Ficolin-3 has been associated with metabolic diseases including gestational, prediabetes, and type 2 diabetes (139,140), and identified as biomarkers in axial spondyloarthritis (141) and as a prognostic biomarker for esophageal cancer (142). Studies on ficolins in reptiles are limited, besides putative roles for veficolins in reptile venom systems (143,144) and for ficolin superfamily proteins as snake venom metalloproteinase inhibitors (145).…”
Section: Discussionmentioning
confidence: 99%
“…Ficolin-3 can activate the complement system via the lectin pathway (133), plays roles in bacterial defenses (134,135) and autoimmunity (136,137) and is modulated in viral infections including HIV (138). Ficolin-3 has been associated with metabolic diseases including gestational, prediabetes, and type 2 diabetes (139,140), and identified as biomarkers in axial spondyloarthritis (141) and as a prognostic biomarker for esophageal cancer (142). Studies on ficolins in reptiles are limited, besides putative roles for veficolins in reptile venom systems (143,144) and for ficolin superfamily proteins as snake venom metalloproteinase inhibitors (145).…”
Section: Discussionmentioning
confidence: 99%
“…This study encompassed RCTs exclusively as part of its research design, with all subjects belonging to the type 2 diabetic population, totaling 1268 patients. The experimental group received interventions involving HIIT exercise, which included running (n=8) ( 17 , 26 – 28 , 33 , 35 , 36 ), cycling (n=23) ( 15 , 17 , 27 , 29 31 , 35 , 37 , 38 ), unassisted exercise (n=5) ( 16 , 20 , 25 ), resistance bands (n=2) ( 30 , 31 ), and walking (n=2) ( 22 ). Meanwhile, the control group was based on aerobic exercise and usual care.…”
Section: Resultsmentioning
confidence: 99%
“…HDL: Twenty-four studies ( 14 – 16 , 19 , 20 , 22 – 26 , 29 , 32 , 33 , 35 , 36 ) assessed the impact of HIIT on HDL indicators in a type 2 diabetes population. The r esults showed that HIIT promoted HDL with a large effect size (MD: 0.62; 95% CI: 0.29–0.95; Hedges’ g =1.19; p<0.01) ( Figure 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, ficolin-3 is one of the proteins belonging to the ficolin family and is highly specific to carbohydrate derived from bacteria and metabolic products [342]. Serum ficolin-3 concentration of persons with prediabetic and type 2 diabetic statuses was higher than that of healthy controls [165,343]. The expression of ficolin-3 was also in accordance with the increased values of FPG, TC, and TG [343].…”
Section: Proteins Involved In Immune Responsementioning
confidence: 85%
“…Serum ficolin-3 concentration of persons with prediabetic and type 2 diabetic statuses was higher than that of healthy controls [165,343]. The expression of ficolin-3 was also in accordance with the increased values of FPG, TC, and TG [343]. Nonetheless, the study of Liu et al [343] found that the up-regulated ficolin-3 was suppressed after receiving exercise intervention and its expression among those in the treatment group was significantly lower when compared with that of the non-treated one at the end of the study [343].…”
Section: Proteins Involved In Immune Responsementioning
confidence: 97%